Views of the future: inclusive education for a democratic society. A review in time - Casanova, María Antonia (Avances en Supervisión Educativa, 2020)
The article includes a route, from a legal and a social point of view, of inclusive education in Spain, starting in 1970. The educational transformation during these 50 years is analyzed, progressing from special education, through the integration programs, until reaching the broadest conception of inclusion, a gaze that encompasses all students with their own characteristics. All differences must be addressed, so a flexible system is essential, which facilitates accessibility to the population as a whole. The paper concludes rasing the pending challenges to achieve the intended inclusive education, in order to reach the inclusive society that requires a democratic model of government.